Pengaruh Profitabilitas dan Kebijakan Dividen terhadap Nilai Perusahaan pada Sektor Perbankan di Bursa Efek Indonesia - Rezky Nurul Amaliah; Nurman Nurman; Annisa Paramaswary Aslam; Anwar Anwar; Abdul Rahman (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the effect of profitability, measured by Return on Equity (ROE), and dividend policy, measured by Dividend Payout Ratio (DPR), on company value, measured by Price to Book Value (PBV), in the banking sector listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. This study also examines the partial and simultaneous effects of these two variables to provide a more comprehensive picture of the factors that determine company value. This study uses a quantitative approach with an associative research design. Secondary data were obtained from the annual financial reports of 15 banking companies listed on the IDX during the research period. Data analysis was performed using panel data regression with the assistance of EViews 2012 software. The statistical tests used included the t-test, F-test, and coefficient of determination (R²). The results showed that profitability (ROE) had a negative and significant effect on company value (PBV), while dividend policy (DPR) had a positive but insignificant effect. However, simultaneously ROE and DPR have a significant effect on PBV even though their contribution is relatively small. This finding indicates that investors pay more attention to profitability as the main indicator in assessing company performance, while dividend policy has not been fully able to influence market perception of the value of banking companies in Indonesia. The conclusion of this study is that profitability is an important factor in determining company value in the banking sector, while dividend policy still requires a stronger signal to influence investor perceptions. The results of this study have implications for company management in formulating effective dividend strategies and for investors in making more appropriate investment decisions in the capital market.